2000
DOI: 10.1507/endocrj.47.343
|View full text |Cite
|
Sign up to set email alerts
|

Possible Reproductive Toxicity of Styrene in Peripubertal Male Mice.

Abstract: Abstract.Environmental estrogens (endocrine disruptive chemicals) have been shown to affect reproduction in wild life and it has been reported that maternal exposure to those chemicals has adverse effects on the male reproductive tract. However, little is known about the potential effects of prepubertal or pubertal exposure to environmental estrogens on the male reproductive tract. Here we examine plasma hormone levels of mice following 4-week oral administration of styrene. Plasma free testosterone levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…The lack of a suppression of T levels in our study is in contrast to a previous experiment in which a profound reduction of T release in peripubertal male mice exposed to styrene was observed (Takao et al, 2000). However, this reproductive toxicity effect was observed only if animals were treated orally with styrene for 4 wk.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of a suppression of T levels in our study is in contrast to a previous experiment in which a profound reduction of T release in peripubertal male mice exposed to styrene was observed (Takao et al, 2000). However, this reproductive toxicity effect was observed only if animals were treated orally with styrene for 4 wk.…”
Section: Discussioncontrasting
confidence: 99%
“…The effects of these treatments on prolactin levels and brain dopamine concentrations have been reported in the first part of this study (Jarry et al, 2002). Male rats were chosen because the vast majority of studies on putative neurotoxic effects of styrene were performed with male animals (Ladefoged et al, 1998;Takao et al, 2000;Chakrabarti, 2000) and because it has been shown that in male rats with low LH and T levels, GABAergic neurotransmission in the MBH is increased (Leonhardt et al, 1999). As a control structure in the brain not related to control of reproductive function, the striatum was selected because of the large number of GLU and GABA neurons in this area.…”
mentioning
confidence: 99%
“…One of these studies involved treatment of lactating dams and evaluation of male rat offspring (Srivastava et al, 1992b), one study involved direct treatment of male rats during the first 60 days of life (Srivastava et al, 1992c), and one study involved the treatment of peripubertal male mice (Takao et al, 2000).…”
Section: Utility Of Datamentioning
confidence: 99%
“…with testicular endpoints after lactational and juvenile styrene treatments (Srivastava et al, 1992b,c) and a mouse study with testicular and plasma testosterone endpoints after peripubertal styrene treatment (Takao et al, 2000) are discussed in Section 3.2.3 because exposures occurred during developmental periods. Cruzan et al (1997), supported by the Styrene Information and Research Center, conducted a limited examination of reproductive organs in rats and mice as part of a subchronic inhalation toxicity study.…”
Section: Male Reproductive Toxicity Rat Studiesmentioning
confidence: 99%
“…Many compounds are suspected to be endocrine disruptors [ Table 1], including plasticizers and plastic materials such as di-(2-ethylhexyl) phthalate (DEHP) (Martinez-Arguelles et al 2014), bisphenol A (BPA) (Ferguson et al 2014;Peretz et al 2014;Michalowicz, 2014), and styrene (Takao et al 2000;Arfini et al 1987); persistant organochlorine pesticides and herbicides such as p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE), chlordane compounds (McGlynn et al, 2008), dichlorodiphenyltrichloroethane (DDT), 2,4-dichlorophenoxyacetic acid (2,4-D), vinclozolin (Mnif et al, 2011); pharmaceuticals including paracetamol, aspirin, indomethacin (Albert et al 2013;Mazaud-Guittot et al, 2013), ibuprofen (Ji et al, 2013), synthetic estrogen 17α-ethinyl estradiol (Reyhanian Caspillo et al, 2014), natural estrogen 17β-estradiol (Thilagam et al 2014); compounds present in personal care products such as parabens (Bledzka et al 2014), UV-B filter 4-(methylbenzylidene)-camphor (4-MBC) (Carou et al, 2009), polycyclic musks fragrances (van der Burg et al, 2008); and dyes (Bazin et al, 2012), for instance methylene blue, acid violet, direct red and Rhodamine B were included on the EPA's list of Universe of Chemicals for Potential Endocrine Disruptor Screening and Testing (EDSP, 2012). Heavy metals like nickel, mercury, cadmium, lead, and uranium are also suspected endocrine disruptors, as well as arsenic (Dyer, 2007;Georgescu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%